The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpubh.2023.1285393
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of microbial contamination in the indoor environment: sources, sampling, health risks, and mitigation strategies

Hitikk Chawla,
Purnima Anand,
Kritika Garg
et al.

Abstract: The quality of the indoor environment significantly impacts human health and productivity, especially given the amount of time individuals spend indoors globally. While chemical pollutants have been a focus of indoor air quality research, microbial contaminants also have a significant bearing on indoor air quality. This review provides a comprehensive overview of microbial contamination in built environments, covering sources, sampling strategies, and analysis methods. Microbial contamination has various origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 281 publications
0
4
0
Order By: Relevance
“…Upon inhalation, some of these bacteria deposit in the bronchi and bronchioles, disrupting the normal gas exchange in the lungs. Additionally, a portion of these microorganisms enters the circulatory system during the exchange of gases and blood, leading to even more severe health consequences for both humans and animals ( 29 ). Research by Bertrand has demonstrated that exposure to low concentrations of endotoxins, a component of microbial aerosols, can lead to increased lung inflammation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon inhalation, some of these bacteria deposit in the bronchi and bronchioles, disrupting the normal gas exchange in the lungs. Additionally, a portion of these microorganisms enters the circulatory system during the exchange of gases and blood, leading to even more severe health consequences for both humans and animals ( 29 ). Research by Bertrand has demonstrated that exposure to low concentrations of endotoxins, a component of microbial aerosols, can lead to increased lung inflammation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing ventilation systems ensures the circulation of clean air, minimizing the risk of airborne pathogen transmission. Enhancing ventilation systems, incorporating routine air quality monitoring, and implementing sanitation protocols represent proactive measures farmers can take to mitigate the presence of harmful microbial aerosols ( 29 ). Furthermore, the identification of prevalent pathogenic bacteria offers valuable insights for implementing preventive strategies, including vaccination protocols or adjustments to animal husbandry practices, thereby minimizing the potential impact of these pathogens on sheep health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, active sampling involves drawing a preset volume of air through a pump, allowing airborne microbes to settle on culture media, fine fibers, or porous membrane structures. This method is suitable for microbial sampling of inhalable dust and allows for the quantification of biological aerosol concentrations [10]. Detecting pathogens is vital for controlling and preventing potential deadly disease outbreaks [11].…”
Section: Introductionmentioning
confidence: 99%